First, you gotta distribute the -4 to x-2,
<span>y+6=-4(X-2)
y+6=-4x+8
Then, subtract both sides by 6,
y+6-6=-4x+8-6
y=-4x+2
Done</span>
Answer:
3
Step-by-step explanation:
Factorial means multiply that number and all numbers below it
3! = 3*2*1 = 6
0! =1
2! = 2*1 = 2
1! =1
6*1
------
2*1
6/2 =3
Answer:
1 1/15
Step-by-step explanation:
Answer:
cross multiply and they should equal the same
Step-by-step explanation:
Answer:
34
Step-by-step explanation:
x=3+√8
y =3-√8
now,
1/x^2+1/y^2
=1/(3+√8)² + 1/(3-√8)²
= [(3-√8)²+(3+√8)²] / (3+√8)²(3-√8)² [L.C.M = (3+√8)²(3-√8)² ]
=[(3-√8+3+√8)²-2(3-√8)(3+√8) ] / [(3+√8)(3-√8)]²
=[6²-2.(3²-√8² )] / (3²-√8²)² [ a²+ b²=(a+b)²-2ab]
=[36-2(9-8) ]/ (9-8)²
=[36-2.1] / 1²
=34